1996
DOI: 10.1021/ac950939g
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Constants of Ginkgolide B in Aqueous Solution

Abstract: The thermodynamic ionization constants (pK(a)(1), pK(a)(2), and pK(a)(3)) of ginkgolide B (9H-1,7a-(epoxymethano)-1H,6aH-cyclopenta[c]furo[2,3-b]furo-[3',2':3,4]cyclopenta[1,2-d]furan-5,9,12-(4H)-trione, 3-tert-butylhexahydro-4,7b,11-trihydroxy-8-methyl-) in aqueous solution have been settled by pH-metric and NMR studies. The three macroscopic pK(a) values as well as the water solubility and the water/n-octanol partition coefficient have been extracted from pH-metric data by means of a nonlinear regression met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…In a third step, the deprotection of the methylenedioxy bridge of 7 was obtained by acid treatment in a dioxane-water mixture and led to 4 in a good yield (89%). The maximal water solubility of 4, as assessed by HPLC with UV detection, was 0.018 g/l, a value at least 15-fold lower than that obtained for ginkgolides C and B (i.e., 0.3 g/l) [Zekri et al, 1996].…”
Section: Results Chemistrymentioning
confidence: 56%
See 1 more Smart Citation
“…In a third step, the deprotection of the methylenedioxy bridge of 7 was obtained by acid treatment in a dioxane-water mixture and led to 4 in a good yield (89%). The maximal water solubility of 4, as assessed by HPLC with UV detection, was 0.018 g/l, a value at least 15-fold lower than that obtained for ginkgolides C and B (i.e., 0.3 g/l) [Zekri et al, 1996].…”
Section: Results Chemistrymentioning
confidence: 56%
“…Indeed, quantitative estimation of the lipophilicity of a biologically active molecule is widely used to establish structure/activity relationships [Van de Waterbeemd and Testa, 1987]. The maximal water solubility of 4, as assessed by HPLC, is significantly lower than that reported for ginkgolide B [Zekri et al, 1996]. Considering previous studies of HPLC retention time, which showed that ginkgolide C is more hydrophilic than ginkgolide B [Braquet, 1987], it can thus be inferred that 4 is significantly more lipophilic than ginkgolide C. Because it is a typical drug-membrane interaction, PAF inhibition by ginkgolides increases as their polarity decreases [Braquet, 1987].…”
Section: Chemistrymentioning
confidence: 99%
“…In all cases care should be taken to avoid water because of hygroscopicity, and the risk of lactone ring opening, which occurs at pH above 6. 12 We used two different instruments, both of the FT-type with PEM modulation of the IR light. The instrument at the Quantum Protein Centre, Copenhagen, Denmark, is a Thermo Nicolet Nexus 870 infrared spectrometer equipped with a single PEM and improved with a filter that only allowed light in the range between 1000 and 1750 cm 21 Here, an extra PEM is added after the sample, eliminating most of the linear birefringence (LB) artifacts that often occur.…”
Section: Materials and Methods Ir And Vcd Spectroscopymentioning
confidence: 99%
“…[144] Ginkgolides contain three lactones (rings C, E, and F, Figure 3) and hence their structures in solution are highly dependent on the pH value of the media in which they are dissolved. Zekri et al determined the ionization constants of ginkgolides by 1 H NMR titrations, [145] which showed that the lactones start to open at around pH 7. At pH 8, the predominant species (% 50 %) is the form in which only ring F is open; ring E is open to a lesser extent (% 20 %).…”
Section: Synthetic Modification Of Parent Compoundsmentioning
confidence: 99%